The Impact of Climate Change on the Lives of Fishermen at Goa Cemara Beach, Bantul, Yogyakarta - Setya, Raudya; Saputri, Mita (Universitas Negeri Semarang, 2025)
Climate change has had a significant impact on the lives of fishermen on Goa Cemara Beach, Bantul, Yogyakarta. These impacts include decreasing fish stocks, extreme weather that disrupts fishing activities, coastal abrasion, and damage to marine ecosystems, such as coral reefs and mangroves. This study aims to analyze the impact of climate change on the socio-economic conditions of fishermen and adaptation strategies that can be carried out to increase their resilience. The research method used is qualitative with a descriptive approach. Data were collected through in-depth interviews, observations, and document studies involving local fishermen, local governments, and environmental experts. Data analysis was carried out using data reduction, data presentation, and conclusion drawing techniques. The results of the study show that climate change not only affects fish catches, but also reduces fishermen's income and increases their socio-economic vulnerability. Adaptation strategies that have been implemented, such as livelihood diversification, technical training, and community collaboration, still face various obstacles, such as minimal access to technology and supporting policies. Therefore, a holistic approach is needed that involves the active participation of fishermen, government, and non-governmental organizations to face the challenges of climate change in a sustainable manner.